2017
DOI: 10.1177/0040517517700196
|View full text |Cite
|
Sign up to set email alerts
|

Tensile, physical, and microstructure properties of glycine treated cotton fibers

Abstract: In this paper, the effect of aqueous glycine treatments at different pH on the tensile properties of cotton fibers is reported. The effects on linear density and X-ray diffraction crystallinity were also evaluated. Glycine treated fibers at alkaline pH (i.e. at pH 11) produced fibers with higher linear density than control (untreated) and glycine treatments at acidic pH. The same treatment also increased strain values in cotton fibers by as much as 36%. Interestingly, similar changes in strain were observed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In addition, the abundance of oxygen functional group and possible formation of hydrogen bonds have been by XPS and FTIR analysis (Figure 4e and Figure 2g). This is in agreement with a previous study, (Remadevi et al 2018) where they treated cellulosic cotton fibre with glycine and found a significant increment in the tensile properties due to the bonding between glycine and cellulosic fibres. In addition, glycine can form zwitterion, which is a compound with no electrical charge since it has both positively and negatively charged functional groups.…”
Section: Tensile Propertiessupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the abundance of oxygen functional group and possible formation of hydrogen bonds have been by XPS and FTIR analysis (Figure 4e and Figure 2g). This is in agreement with a previous study, (Remadevi et al 2018) where they treated cellulosic cotton fibre with glycine and found a significant increment in the tensile properties due to the bonding between glycine and cellulosic fibres. In addition, glycine can form zwitterion, which is a compound with no electrical charge since it has both positively and negatively charged functional groups.…”
Section: Tensile Propertiessupporting
confidence: 93%
“…Interaction between the glycine moieties with the hydroxyl groups of jute fibre takes place in the amorphous region of fibre which renders in absorbing more energy during the mechanical loading of the fibres which ultimately improves overall tensile properties of ATG yarn. (Remadevi et al 2017(Remadevi et al , 2018 The improved mechanical properties could also be described based on the SEM image observations found in Figure 2f of this study where an excellent fibre packing and the paralleled, fibrillated fibres interconnection were achieved for ATG yarns. As a result, there was no stress decay to print the fibre in parallel direction leading to improve the stress carrying capacity of ATG yarn during tensile loading applications.…”
Section: Tensile Propertiessupporting
confidence: 68%
See 1 more Smart Citation
“…[20,21]. On the other hand, some natural fibers are presented in the shape of strands and can be tensile tested, but other natural fibers, due to its length can prove more difficult to test, although there are ingenious test procedures that allow its testing [3,[22][23][24]. Furthermore, it is known that the morphology of the fibers changes during composite preparation and its length and diameter can change due to attrition phenomena or lumen collapse [25].…”
Section: Introductionmentioning
confidence: 99%
“…35 Remadevi et al described glycine-treated cotton fibers at different pH values and studied their tensile, physical, and microstructure properties. 36 However, hydrogel preparation with crosslinking of microcrystalline cellulose by glycine has not been at the primary focus of any research groups to the best of our knowledge. The idea of self-assembled cellulose-glycine hydrogels has also not been covered by the literature.…”
Section: Introductionmentioning
confidence: 99%